Anticancer drugs approved by the Food and Drug Administration for gastrointestinal malignancies: Clinical benefit and price considerations. (7th March 2019) - Jiang, Di Maria; Chan, Kelvin K. W.; Jang, Raymond W.; Booth, Christopher; Liu, Geoffrey; Amir, Eitan; Mason, Robert; Everest, Louis; Elimova, Elena
Abstract: Background: The cost of new anticancer drugs is rising. We aimed to assess the clinical benefit and price of anti‐cancer drugs approved by the US Food and Drug Administration (FDA) for advanced gastrointestinal cancers. Methods: Drugs approved between 2006 and 2017 for advanced GI malignancies were identified from FDA.gov, and their updated supporting trial data were searched. Incremental clinical benefit was quantified by using ESMO Magnitude of Clinical Benefit Scale version 1.1 (grade 0‐5) and ASCO Value Framework version 2 (score range −20 to 180). Higher scores indicate larger net benefit, and substantial benefit was defined as score 4 or 5 by the European Society for Medical Oncology (ESMO). The Micromedex REDBOOK was used to estimate the monthly average wholesale price (AWP) and total drug price (TDP) over the median treatment duration per patient. Clinical benefit, AWP and TDP of each drug class were assessed. Results: In total, 16 GI cancer drugs received FDA approval for 24 indications, including five monoclonal antibodies (mAbs), five oral targeted therapies (TT), two immunotherapeutics (IO), three cytotoxic chemotherapies (CT), and one recombinant fusion protein (aflibercept). Most supporting trials (82%) reported overall survival benefit of less than 3 months and no significant improvement in quality of life. Only five agents (including one TT and one IO) with 21% the of approved indications met the ESMO's threshold of substantial clinical benefit. Median incremental benefit scores of TT and IO were comparable to other drug classes. However their median TDP was much higher at $153 402 and $98 208, respectively, compared to $30 330 USD per patient for CT. The estimated TDP did not correlate with clinical benefit scores. Conclusion: Most FDA–approved gastrointestinal cancer drugs do not meet the ESMO threshold of substantial clinical benefit. TT and IO are estimated to carry significant drug costs, and further cost analysis of these drugs is urgently needed. Abstract : Most FDA–approved gastrointestinal cancer drugs meet neither the ESMO threshold of substantial clinical benefit nor have a high ASCO value framework net health benefit score. Drug price was not associated with magnitude of incremental clinical benefit.